Microencapsulation of pomegranate seed oil using a succinylated taro starch: Characterization and bioaccessibility study - Cortez-Trejo, MC; Abraham, Wall-Medrano; Gaytan-Martinez, Marcela; Mendoza, Sandra (2021)
Pomegranate and taro are domesticated and underutilized crops in Mexico. Particularly, pomegranate seed oil (PSO), which exhibits health benefits, is scarcely exploited in the food industry due to oxidative degradation. This work evaluates the microencapsulation of pomegranate seed oil by spray drying using succinylated taro starch (STS) and β-cyclodextrin (β-CD), as an alternative strategy to protect and deliver PSO. A Central Composite Design (CCD) was applied and the treatment with the highest PSO encapsulation efficiency (61.09 ± 0.41%) was selected. PSO-loaded microparticles obtained with 15% feed solids using 190 ◦C inlet air temperature, showed low aw (0.08 ± 0.01), moisture (1.26 ± 0.05%), hygroscopicity (11.69 ± 0.57%), and water solubility (9.81 ± 0.24%). The microencapsulation improved PSO oxidative stability. The in vitro bioaccessibility study and the kinetic analysis, on the other hand, evidenced that microparticles of succinylated taro starch obtained by spray drying are suitable as carriers for active compounds to be released at the small intestine following a swellingcontrolled release mechanism